СЛІДИ КОНФЛІКТУ – ПОЛІТИЧНІ В’ЯЗНІ У ПРОЗІ ЗОФІЇ НАЛКОВСЬКОЇ - Gajewska, Agnieszka (Ivan Franko National University of Lviv, 2013)
The main aim of the article is highlighting subplots present in the prose works of Nałkowska which are devoted to Ukrainian and Belarusian political prisoners. The author maintains that the Polish colonizing activity along the so-called ‘Eastern Borderland’ requires a detailed and comprehensive study. The results of this analys is should then be compared against contemporary Ukrainian literature as well as the history of the national liberation and nationalist movements at the beginning of 20th century. The article explores three prose texts by Nałkowska, that is, “Węzły życia” (The Bonds of Life), “Niedobra miłość” (Bad Love) and “Ściany świata” (The Walls of the World). The subplots present in all three works can be analyzed in terms of inevident, yet indelible traces pertaining to ethnic conflicts between Poles, Ukrainians and Belarusians, as well as the Jewish pogroms. The themes that span the above- mentioned text can be outlined as follows: first of all, the radical metamorphosis of political attitudes on the part of the protagonists representing former Legionists; secondly, the heroines’ active work for the benefit of the prisoners, also the political ones. In spite of censorship and visibly more and more extreme politics of the authoritarian state towards ethnic minorities, Nałkowska remained one of the few writers who managed to deliver the arrested history of persecutions. Keywords: politics of colonization, national minority, traces of conflict, political prisoners
Keywords: Zofia Nałkowska; kolonizacja; więźniowie polityczni; mniejszości narodowe